Cornelia de Lange syndrome due to mosaic NIPBL mutation: antenatal presentation with sacrococcygeal teratoma. (14th August 2015) - Banait, Nishant; Fenton, Alan; Splitt, Miranda
Abstract : A male infant at 36 weeks gestation was born by section. At 20 weeks of gestation, congenital diaphragmatic hernia and sacrococcygeal teratoma had been seen on ultrasound. At birth, the infant had features suggestive of Cornelia de Lange syndrome (CdLS). He remained hypoxic despite aggressive ventilatory manoeuvres and was palliated. At postmortem, the lungs were hypoplastic. In CdLS, mutations in NIPBL are found in around 50% of cases. Mutation analysis, including multiplex ligation dependent probe amplification of the NIPBL gene from the DNA extracted from peripheral blood lymphocytes was negative, but microarray comparative genomic hybridisation on DNA from skin fibroblast showed a 0.13Mb deletion on chromosome 5p13. The deleted region includes exons 42–47 of the NIPBL gene. It is important to perform NIBPL mutation analysis on DNA from more than one tissue when testing for CdLS.